Thermodynamic performance prediction of rhombic-drive beta-configuration Stirling engine - Mohd Farid, Zainudin; R. M., Faiz; R. A., Bakar; K., Kadirgama (IOP Publishing, 2019)
A single-cylinder rhombic drive beta-configuration Stirling engine, heated and cooled at designated temperature, and fuelled with a fixed amount of Helium gas is used to predict and analyse the thermodynamic cycle performance. A general zero-dimensional numerical model is adapted throughout the prediction of Stirling engine performance. The numerical model is determined based on overall geometrical parameters, working fluid properties, swept and unswept volume. Schmidt and ideal adiabatic analysis based on methodology presented by Berchowitz and Urieli are carried out to predict the cycle pressure, volumetric displacement, work and energy produced during the expansion and compression processes in the cylinder. Based on the designated working condition, the engine is predicted to generate 500 W of power at engine speed of 300 rpm. The indicated thermal efficiency is found to be 66% based on 90° phase angle setting, 4.5 bar of Helium cylinder mean pressure, 893 K of expansion space temperature and 303 K of cooler space temperature.